Optimizing Hybrid Learning in Primary Education: A Systematic Review on AI Integration and Pedagogical Transformation in Society 5.0 - Primus Devra Raihan; Ahmad Umam Mustopa; Maria Ulfa Yudha Julistiyana; Sasmita Sari (Salus Cultura)
Hybrid learning has emerged as the primary technique in the reform of basic education within the Society 5.0 period, particularly in enhancing learning flexibility, digital literacy, and 21st-century skills for children aged 5 to 13 years. Nonetheless, its implementation in elementary school continues to encounter pedagogical and structural obstacles, such as deficiencies in digital infrastructure, instructor preparedness, and constraints in technology-driven assessment. This research used a PRISMA-based systematic literature review (SLR), analyzing Scopus Q1-Q4 and Sinta 2-5 journals that address the incorporation of Hybrid Learning in primary school and digital education policies. The study's findings indicate that Hybrid Learning, incorporating flipped classrooms, gamification, and AI-driven Learning Management Systems (LMS), enhances student engagement and conceptual comprehension. The efficacy of this paradigm relies on equitable digital access, TPACK-based training for educators, and education policies informed by AI and IoT. This research strategically enhances the design of adaptive, data-driven, and inclusive learning to facilitate the sustainable, technology-driven transformation of elementary education.